Toeic icon : (Tổng hợp, 2015)
The TOEIC ICON series is designed to help you cope with these challenges. Beginning with the Basic level (LC and RC), the TOEIC ICON series introduces basic vocabulary and grammar patterns and provides the users with extensive practise to acquire them. Through step-by-step lessons, the skills and strategies to effectiely handle all parts of the test are at the forefront of the series.